The When Prices Stay the Same, but Contents Shrink: Shrinkflation and Consumer Behavior - Leman, Lemiyana; Rina Maradona (Politeknik Negeri Batam, 2025)
Shrinkflation is the practice of reducing the quantity of a product while maintaining its price, has become a prevalent strategy for manufacturers to deal with escalating production expenses. This research explores consumer perceptions and behavior toward shrinkflation through a qualitative approach. Data was collected through semi-structured interviews with consumers of fast-moving consumer goods, aiming to understand their awareness, emotional responses, and decision-making processes regarding shrinkflation. The results reveal that many consumers initially overlook reductions in product size, but once they realize the change, they experience feelings of distrust and dissatisfaction. Additionally, shrinkflation impacts brand loyalty, with several consumers showing a tendency to switch to alternative products or brands. This study highlights the importance of transparency and clear communication in maintaining consumer trust. It provides valuable insights for manufacturers and policymakers in developing strategies that address consumer concerns while promoting fair market practices